The Relationship Between Maternal and Neonatal Microbiota in Spontaneous Preterm Birth: A Pilot Study - Chiara Tirone; Chiara Tirone; Angela Paladini; Angela Paladini; Flavio De Maio; Flavio De Maio; Chiara Tersigni; Chiara Tersigni; Silvia D’Ippolito; Silvia D’Ippolito; Nicoletta Di Simone; Nicoletta Di Simone; et al. (Frontiers in Pediatrics, 2022)
The newborn’s microbiota composition at birth seems to be influenced by maternal microbiota. Maternal vaginal microbiota can be a determining factor of spontaneous Preterm Birth (SPPTB), the leading cause of perinatal mortality. The aim of the study is to investigate the likelihood of a causal relationship between the maternal vaginal microbiota composition and neonatal lung and intestinal microbiota profile at birth, in cases of SPPTB. The association between the lung and/or meconium microbiota with the subsequent development of bronchopulmonary dysplasia (BPD) was also investigated. Maternal vaginal swabs, newborns’ bronchoalveolar lavage fluid (BALF) (1st, 3rd, 7th day of life) and first meconium samples were collected from 20 women and 23 preterm newborns with gestational age ≤ 30 weeks (12 = SPPTB; 11 = Medically Indicated Preterm Birth–MIPTB). All the samples were analyzed for culture examination and for microbiota profiling using metagenomic analysis based on the Next Generation Sequencing (NGS) technique of the bacterial 16S rRNA gene amplicons. No significant differences in alpha e beta diversity were found between the neonatal BALF samples of SPPTB group and the MIPTB group. The vaginal microbiota of mothers with SPPTB showed a significant difference in alpha diversity with a decrease in Lactobacillus and an increase in Proteobacteria abundance. No association was found between BALF and meconium microbiota with the development of BPD. Vaginal colonization by Ureaplasma bacteria was associated with increased risk of both SPPTB and newborns’ BPD occurrence. In conclusion, an increase in α-diversity values and a consequent fall in Lactobacillus in vaginal environment could be associated to a higher risk of SPPTB. We could identify neither a specific neonatal lung or meconium microbiota profiles in preterm infants born by SPPTB nor a microbiota at birth suggestive of subsequent BPD development. Although a strict match has not been revealed between microbiota of SPPTB mother-infant couples, a relationship cannot be excluded. To figure out the reciprocal influence of the maternal-neonatal microbiota and its potential role in the pathogenesis of SPPTB and BPD further research is needed.